The State of Liberal Democracy With Regard to Elections and Political Stability in Africa: Bridging the Gap Between Theory and Practice in Tanzania and Kenya - Paul MTASIGAZYA (Ученые записки Института Африки Российской академии наук)
This study explores the state of liberal democracy and political stability in Africa. In particular it intends to assess what is said about liberal democracy in relation to free and fair election, political stability and the politics of ethnicity in Tanzania and Kenya and the reality happening on the ground (the practice) in East African countries. The rationale for undertaking this analysis is that the East African countries have experienced political transformation: for instance, for much of the post-colonial period East African countries tended to live under one-party regime, but since 1990s East African countries embraced multiparty system. This study pays attention to assessing the outcomes of liberal democracy in East African countries in particular examining the extent to which the liberal democracy promotes free and fair elections, political stability and the mitigation of the politics of ethnicity.